Frequency of epithelioid granulomas in colonoscopic biopsy specimens from paediatric and adult patients with Crohn's colitis. Issue 11 (9th February 2007) - Rubio, C A; Orrego, A; Nesi, G; Finkel, Y
Abstract : Aims: To test the assumption that epithelioid granulomas found in colonoscopic biopsy specimens in patients with Crohn's colitis are markers of a different clinical behaviour. Methods: Sections from colonoscopic biopsy specimens from 352 consecutive patients (119 children and 233 adults) were investigated. Results: A total of 1117 colonoscopies were performed: 293 in children (mean 2.46 per patient) and 824 in adults (mean 3.53 per patient) (p<0.05). Granulomas at initial colonoscopy were recorded in 67.2% (43/64) of children and 65.9% (27/41) of adults (p>0.6), and at subsequent colonoscopies in 53.8% (64/119) of children and 17.6% (41/233) of adults (p<0.05). Surgical intervention was required in 6.3% (4/64) of the children having previous granuloma, but also in 14.5% (8/55) of those without previous granuloma, the rate for operated adults being 26.8% (11/41) and 24.5% (47/192), respectively (p>0.6). Conclusions: Granulomas in entry and/or in subsequent colonoscopic biopsy specimens in patients with Crohn's colitis did not predict the need for subsequent surgical intervention. The fact that the frequency of granulomas was significantly higher in children than in adults with Crohn's colitis (despite a higher mean number of colonoscopic biopsies in adults), and that granulomas were present in colonoscopic biopsy specimens but not in the subsequent surgical specimens from 50% of the paediatric and 36% of the adult patients strengthen the conviction that granulomas in Crohn's colitis might evolve or regress at different time intervals during the course of the disease. This behaviour would reflect a particular immunological reaction, an epiphenomenon from immature tissues—as in children—when challenged by the so far elusive aetiological agent responsible for Crohn's disease.